Endotoxin levels in forklift’s filters and the importance of maintenance enforcement - Pereira, Cristiana Costa (2018)
Many studies have already linked endotoxin exposure, especially in workplaces, to airways disease, yet threshold limit values have not been set, nor a standardized procedure for the analysis of endotoxin levels. Inhaled endotoxins may cause bronchial asthma and may increase the allergic response in hypersensitive people. Endotoxins are biologically active lipopolysaccharides (LPSs) produced by the most external layer of cellular walls of gram (−) bacteria. They are commonly found at workplaces where large amounts of bioaerosols are generated, like in waste sorting plants, where microorganisms growing on organic residue are present at high concentration in the air. Endotoxins are relatively heated stable so they are released into the air during cell growth and after cells’ death when the integrity of the cell wall is ruptured. Up to the present, endotoxin values are measured with non-uniform methods and therefore values are of limited benefit for assessment and limits’ establishment. In this study, eleven filters belonging to the filtration system from forklifts operating in one waste sorting industry located in the Lisbon region and one control filter were analyzed.